Inhibitory Substances Produced by Native Lactobacillus plantarum UTNCys5-4 Control Microbial Population Growth in Meat - Gabriela N. Tenea; Juan Martin Guaña (Journal of Food Quality)
Microbial contamination is the cause of extensive economic loss in the food sector. Previously, the wide-range antimicrobial capacity of inhibitory substances secreted by the Lactobacillus plantarum UTNCys5-4 strain was demonstrated in vitro; however, its mechanism of action in the food matrix remains unclear. This study was aimed to evaluate the effect of antimicrobials produced by the Cys5-4 strain in raw meat applied as pure cell cultures, cell-free supernatant (CFS), and partially purified peptides. The bacteriological results indicated the presence of commensal microbes exhibiting resistance to several antibiotics in meat samples purchased from the local market. Dipping solutions containing antimicrobial substances produced by Cys5-4 resulted in a decrease by 1.91, 1.69, and 1.55 log10 in cell counts upon addition of CFS, peptides and respectively pure cell culture in raw meat at day 9 of storage with refrigeration. The microbial population was maintained in the untreated meat samples during storage. An increase in pH and a concentration of released ammonia was detected in nontreated meat, indicating protein degradation. The Cys5-4 peptides exerted their bacteriolytic mode of action inducing damage in the cell membrane of the target bacteria, allowing the leaching of DNA/RNA content. The results indicate that coating meat with CFS containing Cys5-4 is a promising approach to protect against further contamination by microorganism spoilage, as well as an alternative for increasing the shelf life of raw meat.